MODEL PEMBELAJARAN DAS PADA MATERI BERPIDATO DENGAN MENGGUNAKAN BAHASA INGGRIS SISWA DI KELAS IX MADRASAH TSANAWIYAH NEGERI BINJAI - Sri Rahayu Kesumawati (Universitas Negeri Medan, 2021)
This study aims to find out the DAS learning model (Listen, Observe, Convey) on speaking material using English can improve students' English learning outcomes in class IX of MTsN Binjai odd semester of the 2019/2020 school year. This research consists of two cycles. The results showed that the DAS (Listen, Observe, Convey) learning model on speaking materials using English could improve English learning outcomes and student activities in class IX of MTsN Binjai in the odd semester of the 2019/2020 school year. This can be seen from the results of the calculation in the first cycle between the test scores of the first block and the test scores of the second block, the correlation of the moment r arithmetic products is 0.846, and the t-test value is 8.983, and in the second cycle between the third block test scores and the fourth block test scores. The product correlation of moment r count is 0.925, and the t test value is 13,808, while all the calculated r values are greater than the r table of 0.478, also the t count is greater than the t table test of 2.725, and can also be seen from the results of student attendance in the first cycle the attendance was around 90%, and in the second cycle the attendance was around 95%, and increased to 100%. Keywords: Learning Model, Watershed, Speech